The European Union : a critical guide - McGiffen, Steven Paul (Pluto Press, 2001)
"This book is an introduction to the origins, development and current direction of the EU, and pinpoints the major policy debates animating decision-makers. Offering an analysis of each of the EU's major policy areas, McGiffen places them in the context of the economic, political and philosophical bases that underpin the arguments both for and against the EU. He explains how and why the debate about membership is frequently and falsely presented as if it were a conflict between 'nationalism' and 'internationalism', and argues instead that the EU is merely one of a number of possible solutions to the economic and political problems facing Europe."--Jacket.